Water Quality Assessment of Gomti River in District Sultanpur, Uttar Pradesh (International Journal of Scientific Research in Science and Technology, 2024)
The Gomti river begins in the district Pilibhit Uttar Pradesh, flow through the district of Sitapur, Lucknow, kheri, Barabanki, Sultanpur and Jaunpur unites with the Ganga, today the world struggling with a major type of Inorganic and Natural pollution. Gomti receives a lot of untreated agricultural sewage along with a lot of pesticides, fertilizer, and heavy metals. The purpose of this study is to determine the level of pollution in the Gomti River in Sultanpur district by analysing its Physio-chemical and bacterial parameters. The sample collection took place in 2023 at Four different sites -Golaghat, Sitakund Ghat, Dhobi Ghat, Shamshan Ghat. The following parameters were chosen for the physio-chemical analysis - Temperature, colour, Odor, Turbidity, Total hardness, pH, TDS, EC, Alkalinity, Free Ammonia, and Dissolved Oxygen (DO), Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), Nitrate, Nitrite, Chlorine, Calcium, Magnesium, and some heavy metals, Iron, Chromium, Copper, Lead, Nickel, Selenium, Zinc, Mercury, Cyanide, are the Parameters chosen for the Physio- Chemical analysis. The standard procedure for the examination of water and wastewater, 21st edition (APHA- 2005) was adhered to in order to estimate the water Samples.